PERAN KAPABILITAS INTERAKSI DAN KREASI NILAI BERSAMA UNTUK MENINGKATKAN KINERJA PEMASARAN - Sudarti, Ken; Wardhiani, Okky (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2021)
ABSTRACTThis study focuses on the role of Individual and Relational Interaction Capability in increasing Emotional and Social Value Co-Creation on Market Performance in beauty salon services. Value Co-Creation is one of the service organization's strategies in utilizing external resources from customers. This strategy is crucial because the performance of service organizations is mostly determined by the ability of the frontline staff who interact with customers during service meetings. This research belongs to explanatory research with a population of beauty salon customers in Central Java. The sample consisted of 203 customers, and it was determined using the purposive sampling technique. The author collects customer data through the distribution of offline and online questionnaires analyzed using SPSS 23.0-based regression. This study has proven that Emotional and Social Value Co-Creation can mediate between Individual and Relational Capability with Market Performance. Emotional and social values that are created together will be beneficial for the parties involved. For customers, interactions during the value co-creation process will increase their satisfaction because it can fulfill their needs and desires. This study has also shown the role of individual and relational capability in increasing customer willingness to engage in mutual value creation interactions.JEL  Codes: D20, L10, M20.Keywords : individual interaction capability, relational interaction capability, emotional value co-creation, social value co-creation, market performance.  ABSTRAKStudi ini fokus pada peran Individual dan Relational Interaction Capability dalam meningkatkan Emotional dan Social Value Co-Creation menuju Market Performance pada jasa salon kecantikan. Value Co-Creation merupakan salah satu strategi organisasi jasa dalam memanfaatkan sumberdaya eksternal yang berasal dari pelanggan. Strategi ini sangat penting karena performa organisasi jasa sangat ditentukan oleh kemampuan frontline staff dalam berinteraksi dengan pelanggan pada saat pertemuan jasa. Jenis penelitian bersifat explanatory research dengan populasi pelanggan salon kecantikan di Jawa Tengah. Ukuran sampel yang digunakan sebanyak 203 pelanggan. Teknik pengambilan sampel menggunakan pPurposive sSampling. Peneliti mengumpulkan data pelanggan melalui penyebaran kuisioner secara offline dan online. Alat analisis data menggunakan regresi berbasis SPSS 23.0. Studi ini telah berhasil membuktikan bahwa Emotsional dan Social Value Co-Creation mampu memediasi antara Individuasl dan Relational Capability dengan Market Performance Nilai emosional dan soscial yang dikreasikan bersama akan bermanfaat bagi pihak-pihak yang terlibat. Bagi pelanggan, interaksi selama proses value co-creation akan meningkatan kepuasannya karena kebutuhan dan keinginannya dapat terpenuhi. Studi ini juga telah membuktikan peran individual dan relational capability dalam meningkatkan keinginan pelanggan terlibat dalam interaksi penciptaan nilai bersama.